EFEKTIVITAS INSTRUMEN HOLLAND HEXAGON TERHADAP PEMANTAPAN PILIHAN KARIR PESERTA DIDIK KELAS X SMK NEGERI 5 PONTIANAK - Ball Qiss Ayuni; Muhammad Asrori; Yuline Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to test the effectiveness of the Holland Hexagon Instrument in enhancing the strengthening of career choices for students of class X SMK Negeri 5 Kota Pontianak. The research method used by the researcher was a quantitative study known as One-Group Posttest-Only research design which is one of the type of True Experimental Research design. The total population of the research is 297 students. The sampling technique used is the proportional random sampling technique. The sample group is divided into 28 students for the control class and 28 students for the experiment class. Based on the calculation, the average post-test result for the Experimental Class was 89.79 and the Control Class is 78.00. The results of hypothesis testing by using the sample T-test showed the value of Sig. (2 tailed) on career choice consolidation in the experimental class and the control class of 0.000. As a result, H0 was rejected and Ha is accepted. Thus, it can be concluded that there was a significant difference in the career choice of the experimental class students with the control class in class X SMK Negeri 5 Kota Pontianak. The results of the effectiveness test using effect size analysis showed the value of ES = 0.83. This result proved that the Holland Hexagon Instrument is very effective in improving the career choice of students in class X SMK Negeri 5 Kota Pontianak.